Non-coding RNAs in the pathogenesis of COPD. Issue 8 (20th May 2015) - De Smet, Elise G; Mestdagh, Pieter; Vandesompele, Jo; Brusselle, Guy G; Bracke, Ken R
Abstract : A large part of the human genome is transcribed in non-coding RNAs, transcripts that do not code for protein, including microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). MiRNAs are short single-stranded RNA molecules that negatively regulate gene expression at the post-transcriptional level. They play an important regulatory role in many biological processes. Consequently, altered expression of these non-coding RNAs has been shown to lead to inflammation and disease. In contrast, lncRNAs, can both enhance or repress the expression of protein-coding genes. COPD is typically caused by tobacco smoking and leads to a progressive decline in lung function and a premature death. Exaggerated pulmonary inflammation is a hallmark feature in this disease, leading to obstructive bronchiolitis and emphysema. In this review, we discuss the miRNA expression patterns in lungs of patients with COPD and in mouse models and we highlight various miRNAs involved in COPD pathogenesis. In addition, we briefly discuss a specific lncRNA that is upregulated upon cigarette smoke exposure, providing a short introduction to this more recently discovered group of non-coding RNAs.